Cultural Management of Religious Tolerance in Multicultural-Based Islamic Education Learning in State Schools - Choirun Nisa (ISTAWA, 2021)
This article describes the management of a culture of religious tolerance in multicultural-based Islamic Religious Education (PAI) learning. Indonesia has much diversity, including ethnic diversity, culture, race, customs, religion, language, etc. In the world of education, especially in public schools or public schools, it is inevitable that students or school residents come from various regions and have different diversity, including religion. Students from diverse backgrounds can cause a sense of insecurity for minority students. This situation requires educators to provide religious education that teaches tolerance to students with different religions, races and cultures. Thus This manuscript study explores multiculturalism. This study uses an interpretive paradigm through a qualitative approach, the type of case study. Therefore, in this article, we will discuss the management of a culture of religious tolerance in multicultural-based PAI learning in public schools. The results of this study indicate that through the direction of a culture of religious tolerance in multicultural-based PAI learning that puts forward an ideology that understands, respects, and values human dignity wherever they are. Wherever they come from, emphasizing material from the Qur'an Surat al-hujarat Paragraph 13 can form students who have an attitude of religious tolerance and human values that can create harmony and harmonious relations between students of the same religion or different religions.Artikel ini menjelaskan tentang manajemen budaya toleransi beragama dalam pembelajaran Pendidikan Agama Islam (PAI) yang berbasis multikultural. Indonesia memiliki banyak keragaman diantaranya keragaman suku, budaya, ras, adat, agama, bahasa, dan lain sebagainya. Pada dunia pendidikan terutama dalam sekolah negeri atau sekolah umum tidak bisa dihindari bahwa peserta didik atau warga sekolah tersebut berasal dari berbagai daerah dan memiliki keragaman yang berbeda, termasuk agama. Keadaan peserta didik dari latar belakang yang beraneka ragam ini dapat menimbulkan rasa tidak percaya diri bagi peserta didik yang minoritas, keadaan ini mengharuskan pendidik untuk memberikan pendidikan agama yang mengajarkan toleransi terhadap peserta didik dengan agama, ras, dan budaya yang berbeda-beda, dengan demikian kajian naskah ini mengupas tentang multikultural. Penelitian ini menggunakan paradigma interpretif melalui pendekatan kualitatif, jenis studi kasus. Oleh karena itu, pada artikel ini akan dibahas tentang manajemen budaya toleransi beragama pada pembelajaran PAI berbasis multikultural di sekolah negeri. Hasil penelitian ini menunjukkan bahwa melalui manajemen budaya toleransi beragama pada pembelajaran PAI berbasis multikultural yang mengedepankan ideologi  yang  memahami,  menghormati,  dan  menghargai  harkat  dan  martabat  manusia  di manapun  dia  berada  dan  dari  manapun  datangnya dengan penekanan materi dari al-qur'an surat al-hujarat ayat 13 dapat membentuk peserta didik yang memiliki sikap toleransi beragama dan nilai-nilai kemanusiaan yang dapat menciptakan kerukunan dan keharmonisan hubungan antara peserta didik yang seagama maupun beda agama.